Determinants of housing prices in China - Peng, Junxian; Čermáková, Klára; Sáenz de Viteri Vázquez, Andrea; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
Due to the cultural background, housing has always been the primary need of Chinese people's life, so housing prices have a huge impact on China's economic development and consumers' living costs. The degree of economic development in China has caused differences between the North and the South due to historical reasons, so the theoretical part first analyzes the difference in housing prices between the North and the South from 2011 to 2021, and then analyzes the current situation from the perspectives of policy, economic development, and supply factors.And put forward a hypothesis: "Does the impact of monetary policy on housing prices in China differ across regions?”The practical part uses the relevant data from the National Bureau of Statistics and the provincial statistical bureaus from 2010 to 2011, Firstly use multiple linear regression to analyze the regional differences of factors affecting housing prices. Secondly, the PVAR model is used to test the dynamic correlation between housing prices and monetary policy, and give the conclusion: the impact of monetary policy on housing prices in China is differ across regions.
Vedoucí práce: Klára Čermáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses